Keberagamaan Koruptor Menurut Psikologi (Tinjauan Orientasi Keagamaan dan Psikografi Agama) - Roni Ismail (UIN Sunan Kalijaga Yogyakarta, 2012)
All of religion forbids all followers to do something that could harm others. Any religion has principles that must be complied with by all adherents, either ban or printah. One of the ban as